EZEKIEL, LAW, AND JUDAHITE IDENTITY: A CASE FOR IDENTITY IN EZEKIEL 1–33. - Mayfield, Tyler D. (Religious Studies Review (John Wiley & Sons, Inc.), 2025)
The article discusses a revised dissertation that analyzes the legal elements in the biblical text of Ezekiel 1–33, arguing for the construction of Judahite identity during Neo-Babylonian rule. It highlights previous scholarship on Ezekiel, including topics such as authorship and feminist perspectives, and posits that the text originated in the sixth century BCE. The author employs social psychological frameworks to examine the role of law in society and contextualizes aspects of Ezekiel through Neo-Babylonian legal practices. Key chapters focus on YHWH's legal case against the Judahites and conclude with a case study on Ezekiel 16, illustrating the justification for Babylonian domination. This work aims to contribute to the understanding of prophetic rhetoric in biblical studies.